Heme oxygenase expression as a biomarker of exposure to amphiphilic polymer-coated CdSe/ZnS quantum dots. Issue 2 (March 2013) - McConnachie, Lisa A.; White, Collin C.; Botta, Dianne; Zadworny, Megan E.; Cox, David P.; Beyer, Richard P.; Hu, Xiaoge; Eaton, David L.; Gao, Xiaohu; Kavanagh, Terrance J.
Abstract Because of their unique optical properties, quantum dots (QDs) have become a preferred system for ultrasensitive detection and imaging. However, since QDs commonly contain Cd and other heavy metals, concerns have been raised regarding their toxicity. QDs are thus commonly synthesised with a ZnS cap structure and/or coated with polymeric stabilisers. We recently synthesised amphiphilic polymer-coated tri-n-octylphosphine oxide - poly(maleic anhydride-alt-1-tetradecene (TOPO-PMAT) QDs, which are highly stable in aqueous environments. The effects of these QDs on viability and stress response in five cell lines of mouse and human origins are reported here. Human and mouse macrophages and human kidney cells readily internalised these QDs, resulting in modest toxicity. TOPO-PMAT QD exposure was highly correlated with the induction of the stress response protein heme oxygenase-1 (HMOX1). Other stress biomarkers (glutamate cysteine ligase modifier subunit, NAD(P)H, necrosis) were only moderately affected. HMOX1 may thus be a useful biomarker of TOPO-QDOT QD exposure across cell types and species.